New results on the existence of periodic solutions for a higher-order p-Laplacian neutral differential equation with multiple deviating arguments - Moutaouekkil, L. (Methods of Functional Analysis and Topology, 2021)
In this article, we consider the following high-order p-Laplacian neutral differential equation with multiple deviating arguments: multline* (φ_p(x(t)-cx(t-r))^(n)(t)))^(m) = f(x(t))x’(t)+g(t,x(t),x(t-τ_1(t)),...,x(t-τ_k(t)))+e(t). multline* By applying the continuation theorem and some analytic techniques, sufficient conditions for the existence of periodic solutions are established. It is interesting that the equations not only depend on the constant c but are also dependent on the deviating arguments τ_i, i=1,…, k. Розглядаються нейтральні диференціальні рівняння з p-лапласіаном і кратними відхиленнями аргументів: multline* (φ_p(x(t)-cx(t-r))^(n)(t)))^(m) = f(x(t))x’(t)+g(t,x(t),x(t-τ_1(t)),...,x(t-τ_k(t)))+e(t). multline* Застосовуючи теорему продовження та певні аналітичні методи, отримуються достатні умови існування періодичних розв’язків. Рівняння залежать не тільки від константи c, але й від аргументів із відхиленнями τ_i, i=1,…, k.